Cerium-based and zirconium-based mixed oxides
By developing mixed oxides of zirconium, cerium, lanthanum and rare earth metals other than cerium and lanthanum, the problem of difficult porosity and specific surface trade-offs in existing catalysts at high temperatures is solved, and efficient catalytic performance is achieved.
Patent Information
- Application Number
- CN202210364051.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-04-26
- Filing Date
- 2017-04-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2037-04-25
AI Technical Summary
The challenge of existing three-effect catalysts maintaining high porosity and specific surfaces at high temperatures affecting their catalytic performance.
A mixed oxide of zirconium, cerium, lanthanum and rare earth metals other than cerium and lanthanum is developed to ensure that high specific surfaces and suitable porosity are maintained at high temperatures through specific element ratios and preparation methods.
The mixed oxides with high porosity and specific surfaces are achieved at high temperatures, and the heat resistance and catalytic performance of the catalyst are improved.
Smart Images

Figure CN114715935B_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application date of April 25, 2017, application number 201780026255.7, and titled “Cerium-based and zirconium-based mixed oxide”. Technical Field
[0002] The present invention relates to a mixed oxide of zirconium, cerium, lanthanum and at least one rare earth metal oxide other than cerium and lanthanum with high specific porosity and high specific surface, a preparation method thereof and use thereof in catalysis.
[0003] Technical issues
[0004] "Multifunctional" catalysts are currently used to treat exhaust gases from internal combustion engines (motor vehicle afterburner catalysis). Multifunctional is understood to mean catalysts which are capable not only of oxidation, in particular of oxidation of carbon monoxide and hydrocarbons present in these exhaust gases, but also of reduction, in particular of reduction of nitrogen oxides also present in these gases ("three-way" catalysts).
[0005] The catalyst is produced by the interaction of a noble metal (e.g. Pd, Pt, Rh) with a mixed oxide based on cerium and zirconium, usually as a mixture with aluminum oxide. The mixed oxide must have a suitable porosity. Therefore, it must have a sufficiently large pore volume and also include pores of sufficiently large size so that the gas may diffuse well. The mixed oxide must also have a sufficiently high specific surface area so that it can be used for catalysis.
[0006] It is known that pores of small size reveal the largest specific surface. In fact, these pores are the most sensitive to sintering. It is therefore advantageous to develop a mixed oxide that has a good compromise between high pore volume, high surface area, even after being kept at high temperatures, and for which there is a population of pores of small size with good heat resistance.
[0007] The mixed oxide according to the invention as described in claim 1 aims at this compromise.
[0008] Other features, details and advantages of the present invention will become even more fully apparent on reading the description and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 / 6 to 6 / 6 represent derivative curves (C) which give dV / dlogD as a function of D for several mixed oxides.
[0010] Figure 1 / 6: Curve of the mixed oxide of Example 1 (C)
[0011] (a) After calcination at 900 °C for 4 h;
[0012] (b) After calcination at 1100 °C for 4 h.
[0013] Figure 2 / 6: Curve of the mixed oxide of Comparative Example 17 (C)
[0014] (a) After calcination at 900 °C for 4 h;
[0015] (b) After calcination at 1100 °C for 4 h.
[0016] Figure 3 / 6: Curve of the mixed oxide of Comparative Example 18 (C)
[0017] (a) After calcination at 900 °C for 4 h;
[0018] (b) After calcination at 1100 °C for 4 h.
[0019] Figure 4 / 6: Curve of the mixed oxide of Comparative Example 22 (C)
[0020] (a) After calcination at 950 °C for 3 h;
[0021] (b) After calcination at 1100 °C for 4 h.
[0022] Figure 5 / 6: Curve of the mixed oxide of Example 10 (C)
[0023] (a) After calcination at 950 °C for 3 h;
[0024] (b) After calcination at 1100 °C for 4 h.
[0025] Figure 6 / 6: Curve of the mixed oxide of Example 6 (C)
[0026] (a) After calcination at 900 °C for 4 h;
[0027] (b) After calcination at 1100 °C for 4 h.
[0028] definition
[0029] The specific surface is understood to mean the BET specific surface determined by nitrogen adsorption. This is obtained according to the standard ASTM D3663-03 based on the Brunauer-Emmett-Teller method described in the journal "The Journal of the American Chemical Society", 60, 309 (1938). The abbreviation ST (℃) / x(h) Used to express the specific surface area of a composition obtained by the BET method as described above after calcining the composition at a temperature T expressed in ° C for a period of x hours. 1000℃ / 4h represents the BET specific surface of the composition after calcination of the composition at 1000° C. for 4 h. Unless otherwise stated, calcination at a given temperature and for a given period of time corresponds to calcination in air at constant temperature for the indicated period of time. It is possible to use the Tristar II 3020 device from the company Micromeritics on the samples by following the instructions recommended by the manufacturer.
[0030] The indicated porosities are measured by mercury intrusion porosimetry according to standard ASTM D 4284-83 ("Standard method for pore volume distribution of catalysts by mercury porosimetry"). It is possible to use a Micromeritics Autopore IV 9500 device equipped with a powder penetrometer by following the instructions recommended by the manufacturer.
[0031] Mercury intrusion porosimetry makes it possible to obtain the pore volume (V) as a function of the pore diameter (D). From these data, it is possible to obtain a curve (C) representing the derivative of the function V as a function of log D (dV / dlogD). The derivative curve (C) may present one or more peaks, each located at a point denoted D. p The pores considered to be characteristic of the present invention are pores exhibiting a diameter less than or equal to 200 nm.
[0032] Rare earth metals are understood to mean elements from the group consisting of yttrium and the elements of the periodic table having an atomic number between 57 and 71 inclusive.
[0033] Unless otherwise indicated, the proportions are given in terms of oxide weight. To take this into account, cerium oxide is given as ceria (CeO2) and the oxides of the other rare earth metals are given as REM2O3, REM meaning rare earth metal (divided by Pr6O 11 2 and 3). The zirconium oxide and hafnium oxide are in the form of ZrO2 and HfO2.
[0034] For the sake of continuity of the present description it is specified that, unless otherwise stated, the limit values are included in the ranges within which these values are given. Background Art
[0035] WO 2011 / 006780 describes a composition based on cerium oxide and zirconium oxide which exhibits two very different pore populations after calcination at 900° C. for 4 h. 1100℃ / 4h At least 15m 2 / g. In these examples, this surface is at most 19m 2 / g.
[0036] WO 2011 / 138255 describes compositions based on oxides of zirconium, cerium and yttrium which, after calcination at 900°C for 4 h, exhibit two very different pore populations. They present, after calcination at 1100°C for 4 h, a pore population with a diameter concentrated at a value between 30 and 70 nm, more particularly around 50 nm. 1100℃ / 4h At least 25m 2 / g, more particularly at least 27m 2 / g. In these examples, S 1100℃ / 4h The maximum value is 33m 2 / g and S 1000℃ / 4h The maximum value is 50m 2 / g. The mixed oxide of the present invention is characterized by being greater than 55m 2 / g higher surface S 1000℃ / 4h .
[0037] WO 2012 / 072439 describes compositions based on oxides of zirconium and a rare earth metal other than cerium, which exhibit a 2 / g, more particularly at least 27m 2 Surface S / g 1100℃ / 4h This suggests that it is possible to obtain ranges up to 37m 2 In these examples, S 1100℃ / 4h The maximum value is 33m 2 / g. These compositions do not contain cerium (page 2, line 29). The mixed oxides of the invention are characterized by greater than 55 m 2 Much higher surface S / g 1000℃ / 4h .
[0038] WO 2011 / 083157 describes compositions based on oxides of zirconium, cerium and at least one rare earth metal other than cerium, which exhibit a thermal conductivity of at least 45 m 2 / g, more particularly still at least 55m 2 / g of S 1000℃ / 6h However, the surface S of the compositions of Table 11100℃ / 4h Less than 25m 2 / g.
[0039] WO 2004 / 002893 describes a composition based on oxides of zirconium, cerium, lanthanum and a rare earth metal other than cerium. 1000℃ / 6h At least 40m 2 / g, more particularly at least 55m 2 / g. Surface S 1100℃ / 6h At least 20m 2 / g. An example of this patent application is the composition ZrO2 (73.5%) / CeO2 (20%) / La2O3 (2.5%) / Nd2O3 (4%), which shows 55m 2 Surface S / g 1000℃ / 10h and 23m 2 Surface S / g 1100℃ / 10h .
[0040] WO 2014 / 1221402 describes compositions based on oxides of zirconium, cerium, lanthanum, yttrium or gadolinium and tin (1%-15%) which exhibit a thermal conductivity of at least 45 m 2 / g, indeed even at least 60m 2 / g of S 1000℃ / 6h , and at least 25m 2 / g, indeed even at least 40m 2 Surface S / g 1100℃ / 6h .
[0041] WO 07093593 describes compositions based on oxides of zirconium, cerium, yttrium, lanthanum and rare earth metals other than cerium and lanthanum which can exhibit at least 30 m 2 Surface S / g 1000℃ / 4h These compositions contain between 10% and 25% by weight of yttrium oxide and between 2% and 15% by weight of an additional rare earth metal oxide. All examples include a proportion of rare earth metal other than cerium and lanthanum that is greater than 15% by weight.
[0042] WO 2009 / 130202 describes compositions based on zirconium, cerium and yttrium oxides, in which the proportion of cerium oxide is at most 15% by weight.
[0043] WO 2012 / 171947 describes compositions based on oxides of cerium, zirconium and at least one rare earth metal other than cerium, which have a cerium oxide content of more than 50% by weight. The mixed oxide according to the invention has a proportion of cerium of less than 45%.
[0044] WO 03037506, EP 0 955 267, EP 1 621 251 and US Pat. No. 7,927 699 describe compositions whose specific surface is not as high as the mixed oxides according to the invention.
[0045] EP 2 868 369 describes the production of a mixed oxide of 40% CeO2, 50% ZrO2, 5% Pr2O3 and 5% La2O3 using a micromixing tool. However, no mention is made in this document of the specific surface and porosity of the mixed oxide.
[0046] Mixed oxides are described in FR 2 955 098. The porosity characteristics of the mixed oxide as claimed in claim 1 are not mentioned. DETAILED DESCRIPTION
[0047] As regards the mixed oxides according to the invention, the latter being mixed oxides of zirconium, cerium, lanthanum and optionally at least one rare earth metal (expressed as REM) other than cerium and lanthanum, the weight ratios of these elements, expressed as oxide equivalents relative to the total weight of the mixed oxide, are as follows:
[0048] ■ Between 8% and 45% cerium;
[0049] ■ Between 1% and 10% lanthanum;
[0050] ■ between 0% and 15% of rare earth metals other than cerium and lanthanum;
[0051] ■The rest is zirconium,
[0052] Characterized in that the mixed oxide has:
[0053] ■ After calcination at 1100℃ for 4 hours, at least 30m 2 / g BET specific surface area;
[0054] ■ After calcination at 1000℃ for 4 hours, at least 55m 2 / g BET specific surface area;
[0055] and characterized in that, after calcination at a temperature of 1100° C. for 4 hours, the derivative curve (dV / dlogD) obtained by mercury porosimetry for the mixed oxide shows a maximum value corresponding to a pore diameter D between 24 and 34 nm in the range of pores having a diameter less than or equal to 200 nm. p,1100℃ / 4h The peaks, V and D represent the pore volume and pore diameter, respectively.
[0056] Above-mentioned element Ce, La, REM and Zr exist in the form of oxide usually.But, do not exclude that they can exist in the form of hydroxide or oxyhydroxide at least in part.The ratio of these elements can use conventional analytical techniques in the laboratory to determine, particularly X-ray fluorescence, for example, by using PANalytical Axios-Max spectrometer to determine.The ratio of these elements is provided by the weight of the oxide equivalent relative to this mixed oxide gross weight.
[0057] The mixed oxide comprises the above-mentioned elements in the proportions shown, but it may also comprise other elements, such as impurities. These impurities may be derived from the starting material or from the starting reactants used. Expressed as a weight relative to the total weight of the mixed oxide, the total proportion of these impurities is generally less than 0.1%. The mixed oxide may also comprise hafnium, which is generally present in combination with zirconium in natural ores. The proportion of hafnium relative to zirconium depends on the ore from which zirconium is extracted. Therefore, the weight ratio of Zr / Hf in some ores may be about 50 / 1. Therefore, for example, for 2% hafnium oxide, baddeleyite contains about 98% zirconium oxide. Like zirconium, hafnium is generally present in oxide form. However, it is not excluded that it can be present at least partially in the form of hydroxide or oxyhydroxide. The weight ratio of hafnium in the mixed oxide expressed as an oxide equivalent relative to the total weight of the mixed oxide is less than or equal to 2.5%, or even 2.0%. The proportion of impurities may be determined using inductively coupled plasma mass spectrometry (ICP-MS).
[0058] According to an alternative form, to which the features and embodiments described below also apply, the mixed oxide consists of a mixture of oxides of zirconium, cerium, lanthanum, optionally at least one rare earth metal (REM) other than cerium and lanthanum, and optionally hafnium, the weight proportions of said oxides being as follows:
[0059] ● between 8% and 45% cerium oxide;
[0060] ● between 1% and 10% lanthanum oxide;
[0061] ● between 0% and 15% of at least one rare earth metal oxide other than cerium and lanthanum;
[0062] ● between 0% and 2.5% hafnium oxide;
[0063] ●The rest is zirconium oxide,
[0064] Characterized in that the mixed oxide has:
[0065] ■ After calcination at 1100℃ for 4 hours, at least 30m 2 / g BET specific surface area;
[0066] ■ After calcination at 1000℃ for 4 hours, at least 55m 2 / g BET specific surface area;
[0067] and characterized in that, after calcination at a temperature of 1100° C. for 4 hours, the derivative curve (dV / dlogD) obtained by mercury porosimetry for the mixed oxide shows a maximum value corresponding to a pore diameter D between 24 and 34 nm in the range of pores having a diameter less than or equal to 200 nm. p,1100℃ / 4h The peaks, V and D represent the pore volume and pore diameter, respectively.
[0068] The mixed oxide may also contain strictly less than 1.0%, indeed even less than 0.01%, by weight of tin in the oxide form SnO2 as oxide equivalent relative to the total weight of the mixed oxide. Preferably, the mixed oxide is free of tin.
[0069] The weight proportion of cerium is between 8% and 45% and more particularly between 18% and 45%. The proportion may also be between 8% and 12%.
[0070] The weight proportion of lanthanum is between 1% and 10%, and more particularly between 2% and 9%.
[0071] The mixed oxide may also contain between 0 and 15% by weight of at least one rare earth metal (REM) other than cerium or lanthanum. The rare earth metal may be chosen from yttrium, neodymium or praseodymium.
[0072] The mixed oxide also contains zirconium. The weight proportion of zirconium is the remainder of 100% of the other elements of the mixed oxide. According to one embodiment, zirconium is the main element without considering oxygen, that is, its weight proportion as oxide equivalent is greater than the weight proportion as oxide equivalent of each other constituent element in the mixed oxide (i.e. Ce, La and, if appropriate, REM, Hf and Sn). According to another embodiment, the weight proportion of zirconium can be between 40% and 91%.
[0073] According to one embodiment, the oxide contains no rare earth metals other than cerium and lanthanum. According to this embodiment, the weight proportion of cerium may be between 30% and 40%, and the weight proportion of lanthanum may be between 3% and 6%. The remainder as zirconium may be between 54% and 67% by weight.
[0074] According to another embodiment, the mixed oxide contains only yttrium as rare earth metal besides cerium and lanthanum. According to this embodiment, the proportion of yttrium can be between 1% and 15%, and more particularly between 1% and 13%. The proportion of cerium can be between 20% and 40%.
[0075] According to another embodiment, the mixed oxide contains only two rare earth metals besides cerium and lanthanum, which may be yttrium and neodymium, or yttrium and praseodymium. The proportion of yttrium may be between 1% and 10% by weight, and the proportion of neodymium or praseodymium is between 2% and 6%.
[0076] The following constituent elements of the mixed oxide may be as follows:
[0077] - zirconium and optionally hafnium, cerium, lanthanum, yttrium; or
[0078] - zirconium and optionally hafnium, cerium, lanthanum, yttrium, neodymium; or
[0079] - zirconium and optionally hafnium, cerium, lanthanum, yttrium, praseodymium; or
[0080] - zirconium and optionally hafnium, cerium, lanthanum.
[0081] According to one embodiment, the mixed oxide may show a single phase only after calcination at 900° C. / 4 h and / or 1100° C. / 4 h. The single phase may be a cubic phase or a tetragonal phase.
[0082] According to another embodiment, after calcination at 900°C / 4h, it is possible to distinguish the presence of several crystalline phases, one of which is cubic or tetragonal. According to another embodiment, after calcination at 1100°C / 4h, it is possible to distinguish the presence of several crystalline phases, one of which is cubic or tetragonal.
[0083] An important feature of this mixed oxide is that it has a specific porosity after calcination at 1100° C. for 4 hours. Thus, after calcination at a temperature of 1100° C. for 4 hours, it is possible to distinguish on the derivative curve (C) within the range of pores with a diameter less than or equal to 200 nm a maximum corresponding to a pore diameter between 24 nm and 34 nm (denoted by D p,1100℃ / 4h According to one embodiment, D p,1100℃ / 4h is between 24nm and 30nm, excluding this upper limit (in other words, D p,1100℃ / 4h is greater than or equal to 24 nm and strictly less than 30 nm).
[0084] After calcination at 1100°C for 4 h, the mixed oxide can be made into a p,1100℃ / 4h The pore volume formed by nearby pores represents the major part of the pore volume produced by pores with a diameter less than or equal to 200 nm. This can be demonstrated using the ratio R, which is defined by the following formula:
[0085]
[0086] in:
[0087] ■V1 is the diameter in nm in (D p,1100℃ / 4h-15) and (D p,1100℃ / 4h +15) the pore volume formed by the pores between;
[0088] ■V2 is the pore volume formed by pores whose diameter is less than or equal to 200nm;
[0089] ■ V1 and V2 were measured by mercury porosimetry on the mixed oxides after calcination at 1100°C for 4 h.
[0090] In the range of diameters less than or equal to 200 nm, the pore volume formed corresponds to the inter- and intra-particle pore volume. For this reason, the pore volume indicated here corresponds to the inter- and intra-particle pore volume, since it is derived from the volume values given by the device.
[0091] The ratio R makes it possible to assess the fraction of the pore volume formed by the “small” pore population. The value of 15 nm chosen for the ratio R is close to the half-height width of the observed peak. The higher the R, the smaller the peak in D p,1100℃ / 4h The larger the volume distribution of the pores, the smaller the pores are that are constricted around nearby "small" pores, that is, their diameter in nm is in (D p,1100℃ / 4h -15) and (D p,1100℃ / 4h +15). This ratio R is greater than 0.60. It can be greater than 0.65, or even greater than 0.70. As can be seen in Example 8, it is possible to achieve a value R of 0.90. Thus, the ratio R can be between 0.60 and 0.90, between 0.65 and 0.90, and even between 0.70 and 0.90.
[0092] According to another embodiment, the derivative curve (dV / dlogD) obtained by mercury porosimetry on the mixed oxide after calcination at a temperature of 900° C. for 4 hours shows a maximum value in the range of pores with a diameter less than or equal to 200 nm corresponding to the value denoted D p,900℃ / 4h The peak of the aperture, and the absolute value of the difference D p,1100℃ / 4h -D p,900℃ / 4h It is less than or equal to 15 nm, indeed even less than or equal to 10 nm. This reflects the fact that the pore population forming the pore volume in the range of pores with a diameter less than or equal to 200 nm is not greatly affected by sintering.
[0093] According to one embodiment, after calcination at 900° C. for 4 h, on curve (C), the mixed oxide does not show two distinct peaks in the range of pores with a diameter less than or equal to 200 nm.
[0094] The mixed oxide is also characterized by a high specific surface, in particular as a result of its specific porosity. It thus exhibits at least 30 m 2 / g, more particularly at least 32m2 / g, indeed even at least 35m 2 Surface S / g 1100℃ / 4h . It is possible to reach 40m 2 / g value. This specific surface area can be between 30 and 40m 2 / g.
[0095] The mixed oxide also exhibits at least 55m 2 / g, more particularly at least 58m 2 Surface S / g 1000℃ / 4h . It is possible to reach 65m 2 / g value. This specific surface area can be between 55 and 65m 2 / g.
[0096] Surface S 900℃ / 4h Can be at least 60m 2 / g, more particularly at least 65m 2 / g. When the mixed oxide has never been subjected to a temperature greater than or equal to 900°C, the surface S 900℃ / 4h Can be at least 80m 2 / g. It is possible to reach 85m 2 / g value. This specific surface area can be between 60 and 85m 2 / g.
[0097] As regards the process for preparing the mixed oxide according to the invention, this process comprises the following steps:
[0098] - (a1) adding an aqueous solution of cerium nitrate and an aqueous solution of zirconium nitrate to a stirred container containing an alkaline aqueous solution;
[0099] (a2) subsequently introducing an aqueous solution of lanthanum nitrate and a nitrate of a rare earth metal (REM), optionally present in the mixed oxide, into the mixture formed in step (a1), maintaining stirring;
[0100] - (a3) heating, with stirring, the suspension obtained at the end of step (a2);
[0101] - (a4) subsequently introducing a templating agent into the suspension obtained in the previous step;
[0102] - (a5) optionally, filtering the suspension and washing the precipitate;
[0103] - (a6) calcining the precipitate obtained at the end of step (a5) at a temperature between 700° C. and 1100° C. to produce the mixed oxide;
[0104] (a7) The mixed oxide obtained in step (a6) can optionally be ground.
[0105] In step (a1), a solution comprising zirconium nitrate and cerium nitrate (hereinafter referred to as CZ-nitrate solution) is used. To prepare this solution, crystalline zirconium oxynitrate can be dissolved in water. It is also possible to dissolve zirconium basic carbonate or zirconium hydroxide with nitric acid. The acid attack can preferably be carried out at a concentration of between 1.7 and 2.3 NO3. - The method is carried out at a molar ratio of Zr / Zr. In the case of zirconium carbonate, this ratio may be between 1.7 and 2.0. Thus, a usable zirconium nitrate solution resulting from this etching may have a concentration, expressed as ZrO2, between 260 and 280 g / l. For example, the zirconium nitrate solution used in Examples 1-16 resulting from this etching exhibited a concentration of 266 g / l.
[0106] As a cerium source, it is possible to use, for example, Ce IV Salts, such as nitrates, or ammonium cerium nitrate, are particularly suitable here. Cerium nitrate is preferably used. An aqueous solution of cerium nitrate can be obtained, for example, by reacting nitric acid with hydrated cerium oxide, which is usually prepared by reacting a solution of a cerous salt (e.g., cerous nitrate) and an ammonia solution in the presence of an aqueous hydrogen peroxide solution. It is also possible to preferably use a cerium nitrate solution obtained by the electrolytic oxidation method of a cerous nitrate solution as described in document FR-A-2 570 087, which constitutes a favorable starting material in this example. By this method, it is possible to obtain a Ce content greater than or equal to 0.90. IV / Ce total molar ratio of cerium nitrate solution, which can constitute a favorable starting material. Therefore, the available cerium nitrate solution produced by this method can have a concentration between 250 and 265g / l expressed as CeO2. For example, the cerium nitrate solution used in Examples 1-16 produced by this method showed a concentration of 259g / l.
[0107] The aqueous solutions of cerium nitrate and zirconium nitrate may show a certain initial free acidity, which can be adjusted by adding base or acid. However, it is also possible to effectively use initial solutions of cerium salts and zirconium salts with a certain free acidity as mentioned above and or solutions which have been more or less strictly neutralized in advance. This neutralization can be carried out by adding an alkaline compound to the mixture mentioned above, so as to limit this acidity, but at the same time avoid precipitation. This alkaline compound can be, for example, an ammonia solution or even a solution of an alkali metal (sodium, potassium, etc.) hydroxide. An ammonia solution can advantageously be used.
[0108] It should be noted that when the starting mixture contains Ce III When the method is carried out, it is preferred to include an oxidizing agent during the process, such as aqueous hydrogen peroxide. The oxidizing agent may be used by adding it to the reaction mixture of step (a1).
[0109] Advantageously, salts are used having a purity of at least 99.5% by weight and more particularly at least 99.9% by weight.
[0110] The CZ-nitrate solution can be obtained by dissolving the cerium and zirconium compounds in water in any order or by mixing the two nitrate solutions.
[0111] In step (a1), the CZ-nitrate solution is introduced into a stirred container containing an alkaline aqueous solution to react the alkaline compound with the cerium and zirconium compounds. The alkaline compound dissolved in the alkaline aqueous solution can be a hydroxide, such as an alkali metal or alkaline earth metal hydroxide. Secondary amines, tertiary amines or quaternary amines, as well as ammonia, can also be used. As in these examples, an ammonia solution can be used. As in Example 1, an ammonia solution with a concentration of, for example, 12 mol / l can be used.
[0112] The basic compound may be used in a stoichiometric excess to provide optimal precipitation of all cations. The stoichiometric excess is preferably at least 40 mol % relative to all cations present in the CZ-nitrate solution and also in the solution of lanthanum nitrate and optionally one or more nitrates of one or more rare earth metals (REM) present in the mixed oxide added in step (a2).
[0113] The following step (a2) consists in mixing together the medium resulting from the preceding step (a1) and an aqueous solution of lanthanum nitrate and, if appropriate, of an aqueous solution of the nitrate of one or more rare earth metals (REM) optionally present in the mixed oxide.
[0114] As for the stirring of step (a1), this step is carried out under the stirring of reduction.For example, the stirring speed (S.S.) used in step (a2) is 25rpm, to obtain the mixed oxide according to the example 1-16 of the present invention.With this speed, stirring must make it possible to control the dispersion based on lanthanum and the dispersion based on one or more rare earth metals except cerium and lanthanum in the reaction mixture comprising the precipitate of step (a1).With reference to the mechanical stirring power P as the macroscopic amount representing the mixing quality, for example, it is possible to operate under the mechanical stirring power P (a2) used during step (a2), so that ratio P (a2) / P (a1) is less than or equal to 0.10, even less than 0.05.This ratio can be between 0.0001 and 0.05.This process is adjusted to the new configuration and may need to modify the speed of step (a2) by continuous testing to obtain mixed oxide of the present invention.
[0115] At the end of step (a2) a suspension of precipitate is obtained.
[0116] The following step (a3) of the process is a stage of heating the suspension of the precipitate obtained in step (a2). This heating can be carried out directly on the reaction mixture obtained at the end of step (a2), or on the suspension obtained after separating the precipitate from the reaction mixture of step (a2), optionally washing the precipitate and returning the precipitate to water. The suspension can be heated to a temperature of at least 100° C. and more particularly still at least 130° C., indeed even at least 150° C. The temperature can be between 100° C. and 200° C., more particularly between 130° C. and 200° C. For example, it can be between 100° C. and 160° C. This heating operation can be carried out by introducing the liquid medium into a closed reactor (autoclave type). Under the temperature conditions given above, and in an aqueous medium, it can therefore be specified by way of illustration, the pressure in the closed reactor can be greater than 1 bar (10 5 Pa) is 165 bar (1.65x10 7 Pa), preferably 5 bar (5x10 5 Pa) and 165 bar (1.65x10 7 For temperatures close to 100° C., it is also possible to carry out the heating in an open reactor. The heating can be carried out either in air or in an atmosphere of an inert gas, preferably nitrogen.
[0117] The duration of the heating can vary within wide limits, for example between 1 and 48 h, preferably between 1 and 24 h. Likewise, the temperature increase occurs at a non-critical rate, and it is therefore possible to reach the set reaction temperature by heating the medium (for example for between 30 min and 4 h), these values being given only in an indicative manner.
[0118] It is possible to carry out several heating operations. Thus, the precipitate obtained after the heating step and optionally the washing operation can be resuspended in water, and the medium thus obtained can then be subjected to another heating operation. This additional heating operation is carried out under the same conditions as those described for the first heating operation.
[0119] The following step (a4) of the method comprises adding a template to the precipitate obtained from the previous step, wherein the role of the template is to control the porosity of the mixed oxide. The template comprises polar chemical groups that interact with chemical groups at the surface of the precipitate. The template is removed after the calcination step.
[0120] The template agent can be selected from anionic surfactants, nonionic surfactants, polyethylene glycol and carboxylic acids and their salts, and also surfactants of the carboxymethylated fatty alcohol ethoxylate type. Regarding this additive, reference can be made to the teaching of application WO 98 / 45212, and the surfactants described in this document can be used. As surfactants of this anionic type, mention may be made of ethoxycarboxylates, ethoxylated fatty acids, sarcosinates, phosphates, sulfates such as alcohol sulfates, alcohol ether sulfates and sulfated alkanolamide ethoxylates, or sulfonates such as sulfosuccinates, alkylbenzenesulfonates or alkylnaphthalenesulfonates.
[0121] As nonionic surfactants, mention may be made of acetylenic surfactants, alcohol ethoxylates, alkanolamides, amine oxides, ethoxylated alkanolamides, long-chain ethoxylated amines, ethylene oxide / propylene oxide copolymers, sorbitan derivatives, ethylene glycol, propylene glycol, glycerol, polyglycerol esters and their ethoxylated derivatives, alkylamines, alkylimidazolines, ethoxylated oils and alkylphenol ethoxylates. In particular, mention may be made of the compounds marketed under the trademark PANOL. and Products for sale.
[0122] As regards the carboxylic acids, in particular aliphatic monocarboxylic acids or dicarboxylic acids may be used and among these, more particularly saturated acids may be used. Thus, in particular formic acid, acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, caprylic acid, capric acid, lauric acid, myristic acid or palmitic acid may be mentioned. As dicarboxylic acids, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid may be mentioned. Fatty acids may also be used and more particularly saturated fatty acids may be used. They may in particular be of the formula CH3-(CH2) m A saturated linear acid of -COOH, m being an integer between 6 and 20, more particularly between 9 and 15. It is also possible to use the salts of all the acids mentioned, in particular the ammonium salts. By way of example, mention may more particularly be made of lauric acid and ammonium laurate.
[0123] Finally, it is possible to use surfactants selected from those of the carboxymethylated alcohol ethoxylate type. Products of this carboxymethylated alcohol ethoxylate type are understood to mean products formed from ethoxylated or propoxylated fatty alcohols containing a CH2-COOH group at the end of the chain. These products may correspond to the following formula: R1-O-(CR2R3-CR4R5-O) n-CH2-COOH, wherein R1 represents a saturated or unsaturated carbon chain, the length of which is generally up to 22 carbon atoms, preferably at least 12 carbon atoms; R2, R3, R4 and R5 may be identical and represent hydrogen or R2 may represent a CH3 group and R3, R4 and R5 represent hydrogen; and n is a non-zero integer that may range up to 50 and more particularly between 5 and 15 (these values are included). It should be noted that the surfactant may be composed of a mixture of products having the above formula (wherein R1 may be saturated or unsaturated, respectively) or products containing both CH2-CH2-O- and -C(CH3)-CH2-O- groups.
[0124] The addition of the template can be carried out in two ways. It can be added directly to the suspension obtained by step (a3). In this case, it is preferably added to the suspension, the temperature of which is at most 60° C. It can also be added to the solid precipitate after the latter has been separated from the medium in which the heating has taken place by any known means.
[0125] The amount of template used, expressed as a percentage by weight of template relative to the mixed oxide, is generally between 5% and 100%, more particularly between 15% and 60%.
[0126] According to another advantageous alternative form of the invention, before carrying out the final step of this process (calcination step), after the precipitate has been separated from the medium in which it appears in suspension, the precipitate is washed. This washing operation can be carried out with water, preferably with water at an alkaline pH (for example an aqueous ammonia solution).
[0127] In step (a6), the recovered precipitate is subsequently calcined to obtain the mixed oxide according to the invention. This calcination makes it possible to develop the crystallinity of the formed product. With the increase of the calcination temperature used, the specific surface of the product decreases. This calcination is usually carried out in air, but, for example, calcination in an inert gas or a controlled atmosphere (oxidation or reduction) is not excluded. The calcination temperature is generally between 700°C and 1100°C. Since the mixed oxide exhibits good heat resistance, it is possible to calcine at a temperature greater than 825°C, indeed even greater than 900°C, indeed even greater than 950°C. This temperature can be between 825°C and 1100°C, indeed even between 950°C and 1100°C. The duration of calcination is not critical and depends on the temperature. In a completely indicated manner, it can be at least 2h and more particularly between 2 and 4h.
[0128] During step (a7), the mixed oxide obtained in step (a6) may optionally be ground to obtain a powder having the desired particle size. For example, a hammer mill may be used. The mixed oxide powder may exhibit a mean diameter d between 0.5 and 50.0 μm, measured by laser diffraction in volume distribution. 50 .
[0129] The preparation of the mixed oxide according to the present invention can be based on the conditions of Examples 1-4.
[0130] The invention also relates to a mixed oxide obtainable by the process just described.
[0131] As for the use of the mixed oxide according to the invention, this belongs to the field of motor vehicle pollution control catalysis. The mixed oxide according to the invention can be used to make a catalytic converter, the function of which is to treat motor vehicle exhaust. The catalytic converter comprises a catalytically active coating prepared from the mixed oxide and deposited on a solid support. The function of this coating is to convert certain pollutants in the exhaust gas, in particular carbon monoxide, non-burned hydrocarbons and nitrogen oxides, into products that are less harmful to the environment by chemical reactions.
[0132] The chemical reactions involved can be as follows:
[0133] 2CO+O2→2CO2
[0134] 2NO+2CO→N2+2CO2
[0135] 4C x H y +(4x+y)O2→4x CO2+2y H2O
[0136] The solid support can be a metal monolith, such as FeCralloy, or made of ceramic. The ceramic can be cordierite, silicon carbide, aluminum titanate or mullite. Commonly used solid supports are composed of a generally cylindrical monolith comprising a large number of small parallel channels with porous walls. This type of support is usually made of cordierite and exhibits a compromise between a high specific surface and a limited pressure drop.
[0137] A coating, usually called a "carrier coating", is deposited on the surface of a solid support. The coating is formed by a composition comprising a mixed oxide as a mixture with at least one mineral material. The mineral material may be selected from alumina, titanium oxide, cerium oxide, zirconium oxide, silicon dioxide, spinels, zeolites, silicates, crystalline silicoaluminophosphates or crystalline aluminum phosphates. The composition may also contain other additives specific to each formulator: H2S scavengers, organic or inorganic modifiers with a coating-promoting effect, colloidal alumina, etc. Thus, the coating comprises such a composition. Alumina is a commonly used mineral material, it being possible that this alumina is optionally doped with, for example, alkaline earth metals, such as barium. The coating also comprises at least one dispersed precious metal (such as, for example, Pt, Rh or Pd). Relative to ft 3 The amount of noble metal is generally between 1 and 400 g per volume of the monolith. The noble metal is catalytically active.
[0138] In order to disperse the noble metal, it is possible to add a noble metal salt to the suspension of the mixed oxide or the mineral material or the mixture formed by the mixed oxide and the mineral material. For example, the salt can be a chloride or nitrate of the noble metal (e.g. Rh III The water is removed from the suspension in order to fix the noble metal, the solid is dried and calcined in air at a temperature generally between 300° C. and 800° C. An example of a noble metal dispersion can be found in Example 1 of US Pat. No. 7,374,729.
[0139] The coating is obtained by applying the suspension to a solid support. The coating thus exhibits catalytic activity and can act as a pollution control catalyst. The pollution control catalyst can be used to treat exhaust gases from internal combustion engines. Finally, these catalytic systems and mixed oxides of the invention can be used as NO x Scavengers or even in oxidative environments for promoting NO x restoration.
[0140] For this reason, the invention also relates to a method for treating exhaust gases from an internal combustion engine, the method being characterized by the use of a catalytic converter comprising a coating as described above.
[0141] Examples
[0142] The specific surface was determined automatically using a Tristar II 3020 device from Micromeritics following the instructions recommended by the manufacturer. The samples were pretreated at 300° C. for 15 min under vacuum. It is advisable to desorb entities that may be adsorbed on the surface. The measurements were performed at 5 points in a relative pressure p / p0 range extending from 0 to 0.3 (inclusive). The equilibrium time for each point was 5 s.
[0143] For mercury porosity measurements, a Micromeritics Autopore IV 9500 apparatus equipped with a powder penetrometer was used by following the instructions recommended by the manufacturer. The following parameters may be used: penetrometer used: 3.2 ml; capillary volume: 0.412 ml; maximum pressure ("head"): 4.68 psi; contact angle: 130°; surface tension of mercury: 485 dynes / cm; density of mercury: 13.5335 g / ml. At the start of the measurement, a vacuum of 50 mm Hg was applied to the sample for 5 min. The equilibration times were as follows: low pressure range (1.3-30 psi): 20 s - high pressure range (30-60000 psi): 30 s. Prior to the measurement, the sample was degassed in an oven at 100° C. for a minimum of 15 min.
[0144] The composition is given in weight ratios of the oxides ZrO2, CeO2, REM2O3 (eg La2O3, Y2O3, Nd2O3) and Pr2O6.
[0145] Example 1: Preparation of 5 kg of mixed oxide ZrO2 (60%) - CeO2 (30%) - La2O3 (5%) - Y2O3 (5%)
[0146] A solution of cerium nitrate and zirconium nitrate was prepared by introducing into a container 95.43 liters of water, 11.3 liters of an aqueous zirconium nitrate solution ([ZrO2]=266 g / l; density=1.408 kg / l) and also 5.8 liters of an aqueous cerium nitrate solution ([CeO2]=259 g / l; density=1.439 kg / l). An aqueous solution of lanthanum nitrate and yttrium nitrate was also prepared by introducing into another container 10.77 liters of water, 0.53 liters of a lanthanum nitrate solution ([La2O3]=472.5 g / l; density=1.711 kg / l) and 1.2 liters of a yttrium nitrate solution ([Y2O3]=208.5 g / l; density=1.391 kg / l).
[0147] The ammonia solution (12 l at 12 mol / l) was introduced under stirring into a reactor of about 250 l equipped with a stirrer with inclined blades, and the solution was subsequently made up with distilled water to obtain a basic aqueous solution with a total volume of 125 l. This made it possible to provide a stoichiometric excess of ammonia of 40 mol % relative to the cations present in the two solutions mentioned above.
[0148] The two solutions prepared above were kept under continuous stirring. The solutions of cerium nitrate and zirconium nitrate were introduced into a stirred reactor containing ammonia solution within 45 min, and the stirring was adjusted to a rate of 200 rpm (80 Hz). Then, within 15 min, the solutions of lanthanum nitrate and yttrium nitrate were introduced into a stirred reactor, and the stirring was adjusted to 25 rpm (10 Hz). A precipitate suspension was obtained.
[0149] The suspension was poured into a stainless steel autoclave equipped with a stirrer. The suspension was heated at 150° C. for 2 h under stirring. It was then cooled to a temperature below 60° C. and 1.65 kg of lauric acid were added to the suspension. The suspension was kept under stirring for 1 h.
[0150] The suspension was then filtered and the precipitate was then washed with an aqueous ammonia solution at pH = 9.5, the ratio of which was one time the volume of the filtered mother liquor (washed with 250 liters of aqueous ammonia solution). The solid product obtained was subsequently calcined at 950° C. for 3 h in air to recover about 5 kg of mixed oxides.
[0151] Example 4: Preparation of 5 kg of mixed oxide ZrO2 (59%) - CeO2 (35.5%) - La2O3 (5.5%)
[0152] A solution of cerium nitrate and zirconium nitrate was prepared by introducing into a container 100.3 liters of water, 11.1 liters of zirconium nitrate solution ([ZrO2]=266 g / l; density=1.408 kg / l) and also 6.8 liters of cerium nitrate solution ([CeO2]=259 g / l; density=1.439 kg / l). An aqueous solution of lanthanum nitrate and yttrium nitrate was also prepared by introducing into another container 6.29 liters of water and 0.58 liters of an aqueous solution of lanthanum nitrate ([La2O3]=472.5 g / l; density=1.711 kg / l).
[0153] The ammonia solution (12 liters at 12 mol / l) was introduced under stirring into a 250 liter reactor equipped with a stirrer with inclined blades, and the solution was subsequently made up with distilled water to obtain a basic aqueous solution with a total volume of 125 liters. This made it possible to provide a stoichiometric excess of ammonia of 40 mol% relative to the cations present in the two solutions mentioned above.
[0154] The two solutions prepared above were kept under continuous stirring. The solutions of cerium nitrate and zirconium nitrate were introduced into a stirred reactor containing ammonia solution within 45 min, and the stirring was adjusted to a rate of 200 rpm (80 Hz). Then, within 15 min, the solutions of lanthanum nitrate and yttrium nitrate were introduced into a stirred reactor, and the stirring was adjusted to 25 rpm (10 Hz). A precipitate suspension was obtained.
[0155] The suspension was poured into a stainless steel autoclave equipped with a stirrer. The suspension was heated at 150° C. for 2 h under stirring. It was then cooled to a temperature below 60° C. and 1.65 kg of lauric acid were added to the suspension. The suspension was kept under stirring for 1 h.
[0156] The suspension was then filtered and the precipitate was then washed with an aqueous ammonia solution at pH = 9.5, the ratio of which was one time the volume of the filtered mother liquor (washed with 250 liters of aqueous ammonia solution). The solid product obtained was subsequently calcined at 950° C. for 3 h in air to recover about 5 kg of mixed oxides.
[0157] Examples 2-3 and 5-16: Prepare the mixed oxide according to these examples in the same manner as Example 1, to recycle 5kg of mixed oxide. More specifically, on the one hand, prepare the aqueous solution of cerium nitrate and zirconium nitrate, and on the other hand, prepare the aqueous solution of lanthanum nitrate and the nitrate of the rare earth metal optionally except cerium and lanthanum. The total volume of two solutions is 125 liters. In 45min, the aqueous solution of cerium nitrate and zirconium nitrate is introduced into the reactor identical with the reactor of Example 1 containing 125 liters of ammonia solution, and its stirring is adjusted to the speed of 200rpm (80Hz). The amount of ammonia is such that there is a stoichiometric excess of ammonia of 40 mole % relative to the cation present in the two nitrate solutions. Then in 15min, other solutions of nitrate are introduced into the stirred reactor, and this time its stirring is adjusted to 25rpm (10Hz). Obtain a precipitate suspension.
[0158] The suspension was poured into a stainless steel autoclave equipped with a stirrer. The suspension was heated at 150° C. for 2 h under stirring. It was then cooled to a temperature below 60° C. and 1.65 kg of lauric acid were added to the suspension. The suspension was kept under stirring for 1 h.
[0159] The suspension was then filtered and the precipitate was then washed with 250 liters of aqueous ammonia solution at pH = 9.5. The solid product obtained was subsequently calcined in air at a calcination temperature of at least 825° C. for 3 h to recover about 5 kg of mixed oxides.
[0160] Comparative Example 17: Preparation of 15 kg of mixed oxide ZrO2 (60%) - CeO2 (30%) - La2O3 (5%) - Y2O3 (5%)
[0161] A nitrate solution was prepared by introducing into a container 32.4 liters of an aqueous zirconium nitrate solution ([ZrO2]=278 g / l; density=1.413 kg / l), 17.2 liters of an aqueous cerium nitrate solution ([CeO2]=262 g / l; density=1445 kg / l), 1.59 liters of an aqueous lanthanum nitrate solution ([La2O3]=472.5 g / l; density=1.711 kg / l) and 3.5 liters of an aqueous yttrium nitrate solution ([Y2O3]=217 g / l; density=1.39 kg / l). Subsequently, the solution was made up with distilled water so as to obtain 70.4 liters of a nitrate solution.
[0162] 34 litres of ammonia solution (12 mol / l) were introduced into the stirred reactor of Example 1 and the solution was then made up with distilled water so as to obtain a total volume of 125 litres.
[0163] The solution of nitrates is introduced into this reactor under continuous stirring. The solution obtained is placed in a stainless steel autoclave equipped with a stirrer. The temperature of the medium is brought to 150° C. under stirring for 2 hours. After cooling to a temperature below 60° C., 4.95 kg of lauric acid are added to the suspension thus obtained. The suspension is kept under stirring for 1 h.
[0164] The suspension is then filtered and the precipitate is then washed with an aqueous ammonia solution in a ratio of one times the volume of the filtered mother liquor. The product obtained is subsequently brought to 825° C. for 3 h to recover about 15 kg of mixed oxides.
[0165] Comparative Example 18: Preparation of 13 kg of mixed oxide ZrO2 (60%) - CeO2 (30%) - La2O3 (5%) - Y2O3 (5%)
[0166] An aqueous solution of cerium nitrate and zirconium nitrate was prepared by introducing into a container 52.32 liters of water, 30.2 liters of an aqueous zirconium nitrate solution ([ZrO2]=258 g / l; density=1.38 kg / l) and also 14.9 liters of an aqueous cerium nitrate solution ([CeO2]=261 g / l; density=1.445 kg / l). An aqueous solution of lanthanum nitrate and yttrium nitrate was also prepared by introducing into another container 6.34 liters of water, 1.38 liters of an aqueous lanthanum nitrate solution ([La2O3]=472.5 g / l; density=1.711 kg / l) and 3.1 liters of an aqueous yttrium nitrate solution ([Y2O3]=208 g / l; density=1.391 kg / l).
[0167] Ammonia solution (30 liters at 12 mol / l) was introduced into the same reactor as in Example 1 with stirring, and the solution was subsequently made up with distilled water to obtain a total volume of 108.3 liters of alkaline aqueous solution. This made it possible to provide a stoichiometric excess of ammonia of 40 mol % relative to the cation to be precipitated.
[0168] The two solutions prepared above were kept under continuous stirring. The solutions of cerium nitrate and zirconium nitrate were introduced into a stirred reactor containing ammonia solution within 45 min, and the stirring was adjusted to a rate of 125 rpm (50 Hz). Then, within 15 min, the solutions of lanthanum nitrate and yttrium nitrate were introduced into a stirred reactor, and the stirring was adjusted to 100 rpm (40 Hz). A precipitate suspension was obtained.
[0169] The suspension was poured into a stainless steel autoclave equipped with a stirrer. The suspension was heated at 150° C. for 2 h under stirring. Then, after cooling to a temperature below 60° C., 4.29 kg of lauric acid were added to the suspension. The suspension was kept under stirring for 1 h.
[0170] The suspension was then filtered, and the precipitate was then washed with an aqueous ammonia solution of pH=9.5 in a ratio of one-fold the volume of the filtered mother liquor. The suspension was then filtered, and the precipitate was then washed with water. The obtained product was subsequently calcined in air at 825°C for 3h to recover 13kg.
[0171] The oxides prepared are described in Table 1. The mixed oxides of Examples 1-16 illustrate the invention and were prepared according to the method of the invention under the conditions of Example 1. For their part, the mixed oxides of Examples 17-22 were prepared according to the method of Comparative Example 17 or Comparative Example 18. cal represents the temperature at which the recovered precipitate is calcined (step (a6) of the process). In all cases, the calcination in this step lasts for 3 h. Tcal / 3h represents the BET specific surface of the "fresh" mixed oxide as obtained at the end of the preparation process.
[0172] The mixed oxide of Example 8 can be directly compared with the mixed oxide of Comparative Example 21, since both mixed oxides have the same proportions of oxides and are obtained after calcination at the same temperature of 825° C. (Table I).
[0173] Table I
[0174]
[0175]
[0176] It can be observed that the mixed oxide of Example 8 exhibits a higher specific surface area and a smaller diameter D than the mixed oxide of Comparative Example 21. p,1100℃ / 4h and higher R factors. In addition, the variation of D p,1100℃ / 4h -D p,900℃ / 4h .
[0177] The mixed oxide of Example 10 can be directly compared with the mixed oxide of Comparative Example 22, since both mixed oxides exhibit the same proportions of oxides and are obtained after calcination at the same temperature of 950°C.
[0178] Table II
[0179]
[0180] It can be observed that the mixed oxide of Example 10 exhibits a higher specific surface area and a smaller diameter D than the mixed oxide of Comparative Example 22. p,1100℃ / 4h and higher R-factor.
[0181] Example 19: Using Rh III Salt impregnation mixed oxide
[0182] The mixed oxides of Examples 1, 17 and 18 (having the same ratio of Zr-Ce-La-Y-Nd oxide 60-30-5-6-0) were treated with Rh III Nitrate impregnation. Mixed oxides and Rh III The catalyst is contacted with a nitrate solution, the volume of which is greater than the total pore volume, followed by evaporation of water and calcination for 4 h at 500° C. The proportion of rhodium relative to the catalyst as a whole is 0.1% by weight.
[0183] Example 20: Aging of the Impregnated Mixed Oxide of Example 19
[0184] The aging was carried out on an aging test bench in a redox environment, with 2% CO and 2% O2 injected alternately every 5 min in the presence of 10% H2O (the % values of CO, O2 and H2O are given by volume). The gas flow rate used at STP conditions was 70 cc / min and the weight of the impregnated mixed oxide tested was 2.5 g. The last injection was oxidation (2% O2). The aging temperature was 1100°C and the total duration was 6 hours.
[0185] Programmed temperature reduction device
[0186] The temperature-programmed reduction (TPR) makes it possible to determine the volume of hydrogen consumed by a sample when it is subjected to a programmed temperature rise under a gas flow that is also controlled. The device consists of a series of solenoid valves making it possible to control the passage of the gas, a series of volumetric flowmeters making it possible to fix the flow rates in the different pipes, a series of reversing valves making it possible to direct the gas flow, a (U-shaped) quartz reactor (downflow fluidized bed reactor, the temperature is obtained by a thermocouple located in the reactor) containing the sample and connected to the gas manifold, an oven in which the reactor is placed, a H2O trap and a thermal conductivity detector (TCD) making it possible to analyze the composition of the gas mixture.
[0187] The computer manages the automatic functions and makes it possible to collect in real time the data related to the experiment being carried out using the Micromeritics Autochem II 2920 software. It also performs the processing in order to transform these data into curves with the help of the Grams / 32 software.
[0188] Conditions for TPR analysis
[0189] After the sample had been brought to 500° C. in the presence of 10% O 2 , TPR was performed by bringing the sample from ambient temperature to 900° C. under a hydrogen flow (H 2 / Ar containing 10 vol % H 2 ) according to a temperature gradient of 10° C. / min.
[0190] Results for the impregnated mixed oxide of Example 19 (Table III)
[0191] Table III
[0192]
[0193] Results for the impregnated and aged mixed oxide of Example 20 (Table IV)
[0194] Table IV
[0195]
[0196] It is found that the volume of hydrogen consumed is higher for the samples obtained from the mixed oxides according to the invention, both for the unaged products (Table III) and for the aged products (Table IV).
[0197]
Claims
1. A mixed oxide of zirconium, cerium, lanthanum and optionally at least one rare earth metal REM other than cerium and lanthanum, the weight ratios of these elements, expressed as oxide equivalents, relative to the total weight of the mixed oxide, being as follows: between 8% and 45% cerium; Between 1% and 10% lanthanum; Between 0% and 15% of rare earth metals other than cerium and lanthanum; The remainder is zirconium, It is characterized in that The mixed oxide has: A BET surface area of at least 30 m2 / g after calcination at 1100°C for 4 hours; A BET surface area of at least 55 m2 / g after calcination at 1000°C for 4 hours; and characterized in that, after calcination at a temperature of 1100° C. for 4 hours, the derivative curve dV / dlogD obtained by mercury porosimetry for the mixed oxide shows a maximum value in the range of pores having a diameter less than or equal to 200 nm corresponding to the value denoted D p,1100 ℃ / 4h The peak with pore diameter between 24 and 34 nm, V and D represent the pore volume and pore diameter, respectively; Furthermore, it is characterized in that, after calcination at a temperature of 900° C. for 4 hours, the derivative curve dV / dlogD obtained by mercury porosimetry of the mixed oxide does not show two distinct peaks.
2. The mixed oxide according to claim 1, characterized in that It also contains hafnium.
3. The mixed oxide according to claim 2, characterized in that The weight proportion of hafnium in the mixed oxide, expressed as oxide equivalent relative to the total weight of the mixed oxide, is less than or equal to 2.5%.
4. The mixed oxide according to claim 3, characterized in that The weight proportion of hafnium in the mixed oxide, expressed as oxide equivalent relative to the total weight of the mixed oxide, is less than or equal to 2.0%.
5. The mixed oxide according to claim 2, characterized in that The elements Ce, La, REM, Zr and Hf are present in the form of oxides, hydroxides or oxyhydroxides.
6. The mixed oxide according to claim 5, characterized in that The elements Ce, La, REM, Zr and Hf exist in the form of oxides.
7. A mixed oxide consisting of a mixture of oxides of zirconium, cerium, lanthanum, optionally at least one rare earth metal REM other than cerium and lanthanum and optionally hafnium, the weight proportions of the oxides being as follows: a) between 8% and 45% cerium oxide; b) between 1% and 10% lanthanum oxide; c) between 0% and 15% of at least one rare earth metal oxide other than cerium and lanthanum; d) between 0% and 2.5% hafnium oxide; e) the rest is zirconium oxide, It is characterized in that The mixed oxide has: f) a BET surface area of at least 30 m2 / g after calcination at a temperature of 1100°C for 4 hours; g) a BET surface area of at least 55 m2 / g after calcination at a temperature of 1000°C for 4 hours; and characterized in that, after calcination at a temperature of 1100° C. for 4 hours, the derivative curve dV / dlogD obtained by mercury porosimetry for the mixed oxide shows a maximum value corresponding to a pore diameter D between 24 and 34 nm in the range of pores having a diameter less than or equal to 200 nm. p,1100 ℃ / 4h The peaks, V and D represent the pore volume and pore diameter, respectively; Furthermore, it is characterized in that, after calcination at a temperature of 900° C. for 4 hours, the derivative curve dV / dlogD obtained by mercury porosimetry of the mixed oxide does not show two distinct peaks.
8. The mixed oxide according to any one of claims 1 to 7, which consists of the following elements: - zirconium and optionally hafnium, cerium, lanthanum, yttrium; or - zirconium and optionally hafnium, cerium, lanthanum, yttrium, neodymium; or - zirconium and optionally hafnium, cerium, lanthanum, yttrium, praseodymium; or - zirconium and optionally hafnium, cerium, lanthanum.
9. The mixed oxide according to any one of claims 1 to 7, characterized in that The ratio R defined by the following formula is greater than or equal to 0.60: in: V1 is the diameter in nm at D p,1100 ℃ / 4h -15 and D p,1100 ℃ / 4h +15 pore volume formed by pores between; V2 is the pore volume formed by pores whose diameter is less than or equal to 200 nm; The mixed oxides of V1 and V2 were determined by mercury porosimetry after calcination at 1100°C for 4 h.
10. The mixed oxide according to claim 9, characterized in that The ratio R is greater than or equal to 0.
65.
11. The mixed oxide according to claim 9, characterized in that The ratio R is greater than or equal to 0.
70.
12. The mixed oxide as claimed in claim 1, comprising less than 1.0% by weight of tin in the oxide form SnO2 as oxide equivalent relative to the total weight of the mixed oxide.
13. The mixed oxide as claimed in claim 1, comprising less than 0.01% by weight of tin in the oxide form SnO2 as oxide equivalent relative to the total weight of the mixed oxide.
14. The mixed oxide according to any one of claims 1 to 7, characterized in that The weight ratio of zirconium as an oxide equivalent is greater than the weight ratio as an oxide equivalent of each other constituent element in the mixed oxide without taking into account oxygen.
15. The mixed oxide according to any one of claims 1 to 7, characterized in that The weight proportion of zirconium expressed as oxide equivalent may be between 40% and 91%.
16. The mixed oxide according to any one of claims 1 to 7, characterized in that The rare earth metal other than cerium and lanthanum is selected from yttrium, neodymium or praseodymium.
17. The mixed oxide as claimed in claim 1, which contains no rare earth metals other than cerium and lanthanum.
18. The mixed oxide as claimed in claim 1, which comprises only yttrium as rare earth metal besides cerium and lanthanum.
19. The mixed oxide as claimed in claim 1, which contains only two rare earth metals other than cerium and lanthanum, which may be yttrium and neodymium or yttrium and praseodymium.
20. The mixed oxide according to any one of claims 1 to 7, characterized in that The aperture D p,1100 ℃ / 4h It is between 24nm and 30nm, excluding this upper limit value.
21. The mixed oxide according to any one of claims 1 to 7, characterized in that The derivative curve dV / dlogD obtained by mercury porosimetry for this mixed oxide after calcination at 900° C. for 4 hours shows a maximum value corresponding to the pore diameter D in the range of pores less than or equal to 200 nm in diameter. p,900 ℃ / 4h peak, and make the absolute value difference D p,1100 ℃ / 4h –D p,900 ℃ / 4h Is less than or equal to 15nm.
22. The mixed oxide according to claim 21, characterized in that The absolute value difference D p,1100 ℃ / 4h –D p,900 ° C / 4h Less than or equal to 10nm.
23. The mixed oxide according to any one of claims 1 to 7, which exhibits a carbon content of at least 60 m / s after calcination at a temperature of 900° C. for 4 hours. 2 / g BET specific surface area.
24. The mixed oxide according to any one of claims 1 to 7, which is in the form of a powder, the average diameter d of which is determined by laser diffraction. 50 The distribution by volume is between 0.5 and 50.0 μm.
25. A method for preparing a mixed oxide as claimed in any one of claims 1 to 24, comprising the following steps: (a1) adding an aqueous solution of cerium nitrate and zirconium nitrate into a stirred container containing an alkaline aqueous solution; (a2) subsequently introducing an aqueous solution of lanthanum nitrate and a nitrate of a rare earth metal REM, optionally present in the mixed oxide, into the mixture formed in step (a1), maintaining stirring; (a3) heating the suspension obtained at the end of step (a2) with stirring; (a4) subsequently introducing a templating agent into the suspension obtained in the previous step; (a5) optionally, filtering the suspension and washing the precipitate; (a6) calcining the precipitate obtained at the end of step (a5) at a temperature between 700° C. and 1100° C. to produce the mixed oxide; (a7) optionally grinding the mixed oxide obtained in step (a6); The ratio P(a2) / P(a1) of the mechanical stirring power P(a2) used in step (a2) to the mechanical stirring power P(a2) used in step (a1) is less than or equal to 0.
10.
26. A mixed oxide obtainable by the process according to claim 25.
27. A composition comprising the mixed oxide according to one of claims 1 to 24 or according to claim 25 as a mixture with at least one mineral material.
28. The composition of claim 27, wherein the mineral material is selected from alumina, titanium oxide, cerium oxide, zirconium oxide, silicon dioxide, spinel, zeolite, silicate, crystalline silicoaluminophosphate or crystalline aluminum phosphate.
29. A catalytically active coating deposited on the surface of a solid support, produced from a mixed oxide as claimed in one of claims 1 to 24 or claim 26 or from a composition as claimed in claim 27 or 28.
30. A catalytic converter for treating exhaust gas from a motor vehicle comprising the coating of claim 29.
31. Use of a mixed oxide as claimed in any one of claims 1 to 24 or as claimed in claim 26 or a composition as claimed in claim 27 or 28 for the production of a catalytic converter.
32. A method for treating exhaust gas from an internal combustion engine, characterized in that Use of a catalytic converter comprising the coating as claimed in claim 29.
Citation Information
Patent Citations
Composite zirconium-cerium oxide, process for the preparation thereof, and cocatalyst for cleaning exhaust gas
EP0955267A1
Zirconia porous body and manufacturing method thereof
EP1621251A1
ELECTROLYTIC OXIDATION PROCESS AND ELECTROLYSIS SET FOR ITS IMPLEMENTATION
FR2570087A1
Exhaust gas treatment catalyst
US7374729B2
Porous zirconia powder and production method of same
US7927699B2